Design and simulation of a DC stabilization system for solar energy system - Pham, Thi Viet Hương (H. : ĐHQGHN, 2020)
During the last few years, the demand for solar photovoltaic (PV) energy has grown remarkably since it provides electricity from an exhaustible and clean energy source. The generated power of solar panels depends on environment conditions, which changes continuously due to many factors, for example, the radiation, the characteristics of the load, etc. In order for the solar energy system operates at its most efficiency, it needs to work at its maximum power point (MPP). Previous literature has dealt with either investigating Maximum Power Point Tracking (MPPT) algorithms or tracking a steady output voltage from solar panels. However, when the load is changed, the new MPP need to be defined. In this paper, a novel adaptive MPPT system was proposed to investigate the MPP and keep tracking MPP at the same time. The proposed system was implemented in Proteus simulation. As the results, when the load is changing, the system obtained a steady and reliable desired output voltage. It is not only able to obtain a reliable steady DC output voltage but also keep the solar energy system work at its maximum efficiency